The Proposed Research Model for Successful ERP Implementation in Indian Manufacturing Sector - Archana Sar; Poonam Garg (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to identify critical success factors, risk factors, product selection factor, project management success factors, user satisfaction, tangible benefit and intangible benefits from the literature and propose a conceptual framework for successful ERP implementation in Indian manufacturing sector. The proposed model will give implementers the better understanding of ERP implementation in manufacturing sector. The benefit of this research will be to identify the areas responsible for successful implementation and show the outcome of the implementation in terms of project management success metrics like scope, functionality, budget and schedule. This will result in avoiding implementation mistakes thereby increasing the success rate.